The study of public perception toward domestic tourism promotion in Sarawak / Sharifah Arfiah Said Ismail - Said Ismail, Sharifah Arfiah (2009)
Tourism industry in Malaysia has been traditionally concentrated and promoted towards international markets since its infancy stage in 1960s. Until today, the tourism sector has grown tremendously and has been ranked the second largest foreign income earners behind manufacturing in 2000 and its subsequent years (Tourism Malaysia, 2003). Despite the importance of alluring more and more international travelers to visit Malaysia, the domestic front cannot be overlooked for their vast benefits and numerous untapped potentials. After a string of crises that affect international arrivals on recent years, the domestic tourism industry in Malaysia started to be given priority by the Malaysian government. Continuous promotions and festivities have been carried out throughout the country all year round to spur domestic spending and holidaying. Malaysia has some of the most attractive holiday destinations in the world. Local and foreign tourists alike have contributed significantly to the development of tourism as a major contributor to the nation’s economy.